Raynaud’s phenomenon in the feet of Arctic open-pit miners - Albin Stjernbrandt; Hans Pettersson; Per Vihlborg; Anje Christina Höper; Anna Aminoff; Jens Wahlström; Tohr Nilsson (International Journal of Circumpolar Health)
The literature on Raynaud’s phenomenon (RP) in the feet is scarce, especially in the occupational setting. The primary aim of our study was to investigate the occurrence of RP in the feet of miners. As part of the MineHealth project, written surveys and clinical examinations were completed by 260 Arctic open-pit miners working in northern Sweden and Norway (participation rate 53.6%). Data on RP were collected using standardised colour charts and questionnaire items. Clinical examination included assessing the perception of vibration and pain in both feet. There were eight women and three men who reported RP in the feet. Four also had RP in their hands but none acknowledged any first-degree relatives with the condition. Nine reported exposure to foot-transmitted vibration and one to hand-arm vibration. Seven showed signs of neurosensory injury in the feet. To conclude, the occurrence of RP in the feet of miners was 4.4%. Most cases with RP in the feet did not report the condition in the hands and were exposed to vibration transmitted directly to the feet. There were no reports of a hereditary component. Most cases with RP in the feet also had clinical findings suggestive of peripheral neuropathy in the feet.